Proper motion, spectra, and timing of PSR J1813–1749 using Chandra and NICER. Issue 3 (1st September 2020) - Ho, Wynn C G; Guillot, Sebastien; Saz Parkinson, P M; Limyansky, B; Ng, C-Y; Bejger, Michał; Espinoza, Cristóbal M; Haskell, B; Jaisawal, Gaurava K; Malacaria, C
ABSTRACT: PSR J1813–1749 is one of the most energetic rotation-powered pulsars known, producing a pulsar wind nebula (PWN) and gamma-ray and TeV emission, but whose spin period is only measurable in X-ray. We present analysis of two Chandra data sets that are separated by more than 10 yr and recent NICER data. The long baseline of the Chandra data allows us to derive a pulsar proper motion μ _RA=(-0.067± 0.010) arcsec yr^-1 and μ _Dec.=(-0.014± 0.007) arcsec yr^-1 and velocity v_≈ 900\!-\!1600 km s^-1 (assuming a distance d = 3–5 kpc), although we cannot exclude a contribution to the change in measured pulsar position due to a change in brightness structure of the PWN very near the pulsar. We model the PWN and pulsar spectra using an absorbed power law and obtain best-fitting absorption N_H=(13.1± 0.9)× 10^22 cm^-2, photon index Γ = 1.5 ± 0.1, and 0.3–10 keV luminosity L_X≈ 5.4× 10^34 erg s^-1(d/ 5 kpc)^2 for the PWN and Γ = 1.2 ± 0.1 and L_X≈ 9.3× 10^33 erg s^-1(d/ 5 kpc)^2 for PSR J1813–1749. These values do not change between the 2006 and 2016 observations. We use NICER observations from 2019 to obtain a timing model of PSR J1813–1749, with spin frequency ν = 22.35 Hz and spin frequency time derivative ν =(-6.428± 0.003)× 10^-11 Hz s^-1 . We also fit ν measurements from 2009 to 2012 and our 2019 value and find a long-term spin-down rate ν =(-6.3445± 0.0004)× 10^-11 Hz s^-1 . We speculate that the difference in spin-down rates is due to glitch activity or emission mode switching.